Desain Sistem Berbasis Web Penunjang Pemasaran Limbah Ternak Kelinci (LTK) Sebagai Bahan Baku Pupuk Organik - Hilyah Magdalena; Hadi Santoso (Faculty of Computer Science, University of Jember, 2022)
CV. Mitra Ternak Sejahtera packs livestock waste of their broiler rabbits and ornamental rabbits to be sold as raw material for fertilizer. The sale of rabbit manure waste utilizes a network of resellers that already exist related to the marketing of broiler rabbits and ornamental rabbits. Marketing of rabbit livestock waste is done through messaging applications on social media. Conventional marketing and the high demand for rabbit waste products pose a problem considering that the marketing of rabbit waste uses resellers who also market broiler rabbits and ornamental rabbits. Accuracy of order data and guarantee of availability of waste products that are ready to be marketed are a problem. To reduce product order fulfillment errors and make it easier for resellers and general consumers to find out product stock, this study designed a web-based system for marketing kelimci livestock waste. The system design uses the Agile methodology and the Rapid Application Development (RAD) model with the hope that this system can be developed sustainably and adapt to the needs of the system owner